2017
DOI: 10.1007/s11356-017-0977-z
|View full text |Cite
|
Sign up to set email alerts
|

β-carotene and retinol reduce benzo[a]pyrene-induced mutagenicity and oxidative stress via transcriptional modulation of xenobiotic metabolizing enzymes in human HepG2 cell line

Abstract: Benzo[a]pyrene (B[a]P) is one of the polycyclic aromatic hydrocarbons which is formed due to smoking of foods, incomplete combustion of woods, vehicle exhausts, and cigarettes smokes. B[a]P gets entry into human and animal bodies mainly through their diets. Metabolic activation of B[a]P is required to induce mutagenesis and carcinogenesis in animal and human studies. Carotenoids and retinoids are phytochemicals that if ingested have multiple physiological interferences in the human and animal bodies. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…The achieved results indicated that pyrene had significant cytotoxic effects on HepG2 cells at 50 n causing 28% reduction in cell viability. Unlikely, benzo[a]pyrene, a promutagenic PAH, did not alter HepG2 cell viability [8, 15]. Pyrene caused a clear induction of oxidative damage, in terms of the production of ROS, in a concentration-dependent manner (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The achieved results indicated that pyrene had significant cytotoxic effects on HepG2 cells at 50 n causing 28% reduction in cell viability. Unlikely, benzo[a]pyrene, a promutagenic PAH, did not alter HepG2 cell viability [8, 15]. Pyrene caused a clear induction of oxidative damage, in terms of the production of ROS, in a concentration-dependent manner (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Each experiment was represented by 6 plates/treatments. Primer sets for the selected targets were designed based on previous work [8] and are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the studies aiming at analyzing the influence of individual products with a specific content on the cascade of changes induced by BaP, there are many papers describing the influence of isolated single compounds, such as vitamin C, β-carotenoids, retinol, retinoic acid, phenethyl isothiocyanate, luteolin, chrysin, naringenin, quercetin, damnacanthal, proanthocyanidine, resveratrol, berberine, catechin, anthocyanins, apigenin or kaempferol. The mechanisms of action of the selected phytochemicals and the above-mentioned dietary compounds are presented in Table 1 [52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73].…”
Section: Benzo(a)pyrene (Bap)mentioning
confidence: 99%
“…Amelioration of cardiotoxicity was observed in rats on treatment with beta-carotene (Bahadır et al, 2018). It was recommended to consume food rich in beta-carotene and retinol in areas highly polluted with polycyclic aromatic hydrocarbons (Darwish et al, 2018). However, avoiding oxidant sources such as cigarette smoke and alcohol must be considered when taking dietary antioxidants (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%